Reproductive behavior of crossbred dairy cows grazing an intensive silvopastoral system under tropical dry forest conditions (2017)
ABSTRACT: It is widely accepted that selection for high milk yield in dairy cows has negatively affected their reproductive performance. After calving, dairy cows experience a nutritional imbalance due to an asynchrony in the occurrence of the lactation and dry matter intake peaks. In the tropics, this situation is exacerbated due to por quality and/ or availability of the diet. A study was carried out to describe the nutritional and reproductive behavior of two-to-four parturition crossbred cows (Gyr (Bos indicus) x Holstein (Bos taurus)) divided in two groups according to their calving to first service interval (CFSI): Group 1: ≤50 days CFSI, n=7; Group 2: ≥50 days CFSI, n=8. Animals were grazing in an intensive silvopastoral system (ISS) based on Leucaena leucocephala and Cynodon plectostachyus and also received protein, energy and mineral supplementation. Dry matter (DMI) and nutrient intake were individually estimated and correlations between reproductive and nutritional parameters were performed. Additionally, serum progesterone concentration was monitored. Group 2 had greater forage and total DMI and milk production than Group 1 (P<0.05). Hence, Group 2 had greater nutrient intake from forages than Group 1 (P<0.05). Group 1 had a positive nutritional balance and an optimum reproductive performance compared to Group 2, which had a negative energy balance and lengthier days with open intervals (P<0.05). It was corroborated that protein and energy are required in adequate levels, to ensure that uterus undergoes involution correctly and ovarian activity starts soon in the postpartum period.